Torsion of a rudimentary uterine horn with multiple leiomyomas in a case of Mayer-Rokitansky-Küster-Hauser syndrome - M.S. Kim; E.D. Na; H.C. Kim; M. Kim; S.Y. Shin; M.H. Lee (Clinical and Experimental Obstetrics & Gynecology, 2020)
The Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is characterized by congenital hypoplasia or aplasia of the uterus and vaginal agenesis. A 53-year-old woman presented to the emergency department with severe abdominal pain. She was diagnosed with torsion of the right rudimentary uterine horn with multiple leiomyomas with MRKH syndrome. The twisted rudimentary uterine horn and multiple leiomyomas were successfully removed via laparoscopy. MRKH syndrome with uterine horn torsion is uncommon and ours is the first case of torsion in MRKH syndrome treated via a laparoscopic approach. Our report indicates that laparoscopy is ideal for the simultaneous diagnosis and treatment of pelvic masses in MRKH syndrome.